The roles of microglia and astrocytes in neuroinflammation of Alzheimer’s disease - Han, Jialin; Zhang, Zhi; Zhang, Pengfei; Yu, Qian; Cheng, Qian; Lu, Zhiming; Zong, Shuai (Frontiers in Neuroscience, 2025)
Alzheimer’s disease (AD) is a typical neurodegenerative disease, with the most highlighted pathologic changes identified in the β-amyloid peptide (Aβ) and neurofibrillary tangles (NFTs). Aβ cascade hypothesis, which has seemed to convincingly elucidate the AD pathogenic mechanism, is becoming increasingly disproved, indicating that it is no longer able to explain the emergence of AD entirely. Neuroinflammation offers an alternative explanation for the development of AD. This paper presents an overview of the influence of microglia and astrocytes on neuroinflammation of AD. We further examine the interplay between microglia and astrocyte and their roles as inflammatory mediators. It is hypothesized that targeting these molecular mechanisms associated with neuroinflammation and controlling risk factors may provide a viable therapeutic approach for AD.